The Effectiveness of MyMAT Aedes Mosquito Trap in Reducing Dengue Cases - Shahar, Mohd Khadri; Ismail, Suzilah; Ahmad, Rohani; Omar, Topek (Wolters Kluwer - Medknow, 2022)
Malaysia Mosquito Autocidal Trap (MyMAT) is a green technology Aedes mosquito trap that does not use harmful chemical substances. This study aimed to evaluate the efficiency of MyMAT in reducing dengue cases and relating the cases to rainfall. An experimental field study was conducted for 42 weeks at Pangsapuri Nilam Sari, Shah Alam, Selangor. A total of 624 MyMAT was allocated at four blocks: inside each apartment and outside at the corridors in each level. Mosquito and rainfall data were collected weekly using MyMAT and a mobile rain gauge, respectively. The dengue cases data was retrieved from the e-dengue system obtained from the Malaysia Ministry of Health. The findings showed that MyMAT could catch 97% of Aedes mosquitoes and reduced dengue cases on average of 78%, indicating MyMAT is a reliable Aedes mosquito trap. Interestingly the findings also revealed a significant relationship between dengue cases, the number of Aedes mosquitoes, and rainfall. This week notified dengue cases increased when last two weeks mosquitoes increased due to previous two weeks rainfall increment. Thus indicating an indirect but significant relationship between this week notified dengue cases with the last four weeks rainfall. These relationships can be used in establishing a dengue outbreak forecasting model, which can act as an early warning system